Impacts of chemical reaction, thermal radiation, and heat source/sink on unsteady MHD natural convective flow through an oscillatory infinite vertical plate in porous medium - Saikia, Dibya Jyoti; Ahmed, Nazibuddin (Zielona Góra: Uniwersytet Zielonogórski)
The main objective of this exploration is to analyze the effects of heat source/sink, chemical reactions, and radiation on the unsteady free convective flow through a porous medium using an infinitely oscillating vertical plate. The Laplace transformation tactics is utilized to solve the governing equations for concentration, energy, and momentum. The simulation results demonstrate that the chemical reaction parameter dwindles both primary and secondary velocities.
Keywords: porous medium; thermal radiation; free convection; chemical reaction; heat source/heat sink